2009
DOI: 10.1590/s1516-35982009000900003
|View full text |Cite
|
Sign up to set email alerts
|

Relações planta-animal em ambiente pastoril heterogêneo: processo de ingestão de forragem

Abstract: RESUMO -Com o objetivo de avaliar o efeito da estrutura de uma pastagem nativa nos parâmetros que compõem o processo de ingestão de forragem de ovelhas e bezerras em pastejo, foram estabelecidas quatro alturas de pasto (4, 8, 12 e 16 cm), em delineamento estatístico inteiramente casualizado, com quatro tratamentos e duas repetições no tempo e no espaço. A massa do bocado e a taxa de ingestão foram estimados por diferença de peso vivo corrigido para a perda de peso metabólico, durante 45 minutos. Os moviment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
(16 reference statements)
3
16
0
14
Order By: Relevance
“…The decrease during the fall was due to the lower residual forage mass observed at that season. Neverheless, for all the conditions of the pastures, regardless of season, height values remained close to those proposed by Gonçalves et al (2009). These authors found that higher intake rate of cattle in natural pasture occurred with pasture height of 11.4 cm and proposed target management close to this value.…”
Section: Resultssupporting
confidence: 72%
“…The decrease during the fall was due to the lower residual forage mass observed at that season. Neverheless, for all the conditions of the pastures, regardless of season, height values remained close to those proposed by Gonçalves et al (2009). These authors found that higher intake rate of cattle in natural pasture occurred with pasture height of 11.4 cm and proposed target management close to this value.…”
Section: Resultssupporting
confidence: 72%
“…The differences in residual mass in the first year are due to possible errors in the estimates of projected accumulation rates, leading to an overestimation of the stocking rate, which can be evidenced by the lower forage allowances obtained that year. However, the differences observed in the residue did not affect the results, since the forage masses maintained (1461 to 1796 kg/ha of DM in 2007 and above 2000 kg DM/ha in 2008) are close to or above the minimum that limits intake in this kind of pasture (Gonçalves et al, 2009), not compromising the comparison of treatments. Nitrogen availability is essential for growth and development of plant tissues, increasing appearance and elongation leaf rates (Lemaire & Chapman, 1996).…”
Section: Resultsmentioning
confidence: 93%
“…Os reduzidos tempos despendidos para a atividade de deslocamento podem ser explicados devido o ambiente pastoril avaliado ser homogêneo. Nessa situação a quantidade de informações de que o animal deve dispor para acionar seus mecanismos de decisão é menos complexa, não havendo necessidade de procura por alimentos diversos e mais palatáveis, uma vez que a pastagem é composta por apenas uma espécie de forragem (GONÇALVES et al, 2009). O maior tempo de ócio, 50% do total, foi verificado aos 30 cm de altura.…”
Section: Resultsunclassified
“…Compreender as relações existentes entre as características estruturais e o comportamento dos animais é fundamental para se definir as estratégias de manejo das pastagens (GONÇALVES et al, 2009). Entre as características estruturais a altura do dossel e a massa de folhas são os principais fatores que influenciam o comportamento em pastejo (CARVALHO et al, 2001).…”
Section: Introductionunclassified